2019
DOI: 10.1186/s43159-019-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol therapy in infantile hemangioma: correlation of age and duration of treatment to the outcomes

Abstract: Background: Infantile hemangioma (IH) is the commonest vascular tumor affecting children that appears in the first 2 weeks of life and follows a proliferative phase that continues during the first year of life. After then, it undergoes involution, which lasts for several months or years depending on the size, site, gender, and development of complications. The purpose of this prospective study was to evaluate the correlation of age and duration of propranolol therapy to the outcomes of infantile hemangioma. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Topiramate and propranolol similarly prevents migraine headaches [41], and propranolol reduces the monthly headache frequency [42]. The treatment with propranolol has been investigated in infants and children [43][44][45][46][47][48][49][50]. Propranolol reduces the recurrences of supraventricular tachycardia in infants [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Topiramate and propranolol similarly prevents migraine headaches [41], and propranolol reduces the monthly headache frequency [42]. The treatment with propranolol has been investigated in infants and children [43][44][45][46][47][48][49][50]. Propranolol reduces the recurrences of supraventricular tachycardia in infants [43].…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol treatment reduces the symptoms of heart failure in infants with congenital heart disease [45], and treats hypoxemic spells in infants with tetralogy of Fallot [46]. Propranolol treats infantile haemangioma; a higher response-rate can be gained with early treatment and prolonged course of therapy [47] and propranolol reduces infant haemangioma size without producing adverse-effects [48]. Low dose of propranolol is safe and effective for treating problematic proliferating infantile haemangioma [49] and shorts the natural course of infantile haemangioma [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For hemangiomas that require treatment, the best time to start is before or immediately after the onset of obvious risks of complications [24]. It was found that IH treatment in the proliferative phase allows achieving the best result [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The diagnosis is basically clinical; Contrast MRI imaging evaluation is used to define the type, size, and extent of the lesion; 6 The treatment of a patient with IH is individualized, depending on factors such as size of lesion, location, presence of complications such as ulceration, risk of scarring or disfigurement, age of the patient, rate of growth or involution at the time of diagnosis, risks and benefits of administering the treatment. 7 We present the case of an infant with a diagnosis of deep IH in connection, treated with propranolol.…”
Section: Introductionmentioning
confidence: 99%